Di-nuclear Cu(II) complex bearing guanidinium arms for sensing pyrophosphate and monitoring the activity of PPase. (April 2019) - Li, Zhuoan; Qiang, Jian; Li, Jing; Wei, Tingwen; Zhang, Zhijie; Chen, Yahui; Kong, Qing; Wang, Fang; Chen, Xiaoqiang
Abstract: In this work, we reported a di-nuclear Cu(II) complex bearing double guanidinium arms for sensing pyrophosphate (PPi) with high selectivity and sensitivity. Using pyrocatechol violet (PV) and esculetine as colorimetric and fluorescent indicators respectively, the copper complex-indicator ensemble exhibited remarkable colorimetric and fluorescent changes upon addition of PPi in the aqueous solution. Comparing to the di-nuclear Cu(II) complex without guanidinium arms, the introduction of positively-charged guanidinium groups lead to 2.6 × 10 4 -fold enhancement on the binding affinity toward pyrophosphate (PPi). The ensemble containing copper complex and PV was further used to monitor the hydrolysis of PPi catalyzed by pyrophosphatase (PPase). Graphical abstract: Comparing to the di-nuclear Cu(II) complex without guanidinium arms, the introduction of positively-charged guanidinium groups lead to 2.6 × 10 4 -fold enhancement on the binding affinity toward pyrophosphate (PPi). Highlights: A new Di-nuclear Cu(II) complex-based chemosensor which bearing guanidinium arms for pyrophosphate (PPi) was synthesized. The introduction of guanidinium groups led to 2.6 × 10 4 -fold enhancement on the binding affinity toward PPi. The chemosensor was applied to monitor the hydrolysis reaction of PPi.